Thermally Evaporated Tin Oxide Thin Film for Gas Sensing Applications - Sumanta Kumar Tripathy; T.N.V. Prabhakara Rao (Журнал нано- та електронної фізики)
In this study tin oxide thin film is deposited on glass substrate by Thermal Evaporation technique for gas sensing applications. While deposition the distance between source and the substrate is maintained at 8cm, the pressure of the chamber is kept at 2.5  10 – 5 torr and rate of deposition is about 6-10 Å/sec at substrate temperature 35-40 C. Structural, micro structural, optical and gas sensing properties are studied. Here thickness of the film is maintained in between 400-450 nm. The film is annealed at 500 C for one and half hours. Surface morphology is examined from SEM micrographs by using Scanning Electron Microscope Model – Philips XL 30. From this study the grain size is found to be around 40-45 nm. The structural study of the films was carried out by XRD measurement using SIEMENS diffractometer (Model) D 5000. From the observation it is confirmed tetragonal rutile structure of tin oxide. Optical characteristics are studied by UV/VIS Spectrophotometer Model ELICO-SL-159 in the wavelength range 300-1000 nm and refractive index, thickness of the thin film and band gap are calculated. From this study of optical properties it is observed that the maximum transmittance is about 80 %. The measured refractive index is 2.17 which nearly the same with the theoretical result. The film is investigated for sensing of carbon monoxide gas. Sensitivity test is carried out by a hand make sensitivity tester. Sensitivity of the film to CO gas is measured at different temperatures and was found to be highly sensitive at 220 C.